Intrarater and Interrater Reliability of Heckmatt Scoring System in Amyotrophic Lateral Sclerosis. Issue 4 (July 2021) - Kenis-Coskun, Ozge; Gunes, Taskin; Isak, Baris; Yagci, Ilker
Abstract : Purpose: This study aims to determine the intrarater and interrater reliability of the Heckmatt score in the upper extremity muscles in patients with amyotrophic lateral sclerosis and to investigate its relationship with the clinical features and quantitative echo intensity measurements. Methods: The Heckmatt scores of multiple upper extremity muscles were calculated in 28 patients with amyotrophic lateral sclerosis and examined the relationships of these values with quantitative ultrasound (QUS) measurements and the Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised. Results: The Heckmatt scores showed strong intrarater and interrater correlations with Cohen's Kappa scores ranging from 0.7 to 0.91. In all investigated muscles, the Heckmatt scores showed moderate correlations with quantitative echo intensity measurements and Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised dressing subscale. Conclusions: The Heckmatt score is a reliable method in evaluating muscles of the upper extremities in patients with amyotrophic lateral sclerosis. It moderately correlates with quantitative values and functional status.